Visualisation of fetal meconium on post-mortem magnetic resonance imaging scans: a retrospective observational study. (November 2020) - Hyde, Georgia; Fry, Andrew; Raghavan, Ashok; Whitby, Elspeth
Background: Less invasive techniques for fetal post-mortems are increasingly used to correlate with parental wishes. With the use of post-mortem magnetic resonance imaging (MRI), normal appearance of the organs must be established. Purpose: To investigate the after death appearance of the fetal meconium throughout gestation using the hyperintense appearance of meconium on T1 weighted MRI. Material and Methods: This was a retrospective study that took place in a tertiary referral centre radiology department. Sixty-two fetal body post-mortem MRI scans (January 2014 to May 2018) between 12 and 41 weeks gestation were reviewed. Signal intensity of meconium at the rectum, sigmoid colon, splenic flexure and hepatic flexure was evaluated and correlated with gestational age. Interrater reliability was calculated. Results: Meconium did not consistently have high signal intensity on T1 scans and was not always obvious. Rectal meconium had the highest intensity, and the more proximal the bowel the lower the intensity. The meconium had higher intensity at earlier gestations. Interrater reliability for rectal meconium gradings was excellent. Conclusion: This study provides the first published primary research on the appearance of fetal meconium on post-mortem MRI. Overall, results were variable and suggest an alteration of bowel contents after death, but further investigation is needed to effectively inform practice.